2007
DOI: 10.1074/jbc.m703627200
|View full text |Cite
|
Sign up to set email alerts
|

RAVE Is Essential for the Efficient Assembly of the C Subunit with the Vacuolar H+-ATPase

Abstract: The RAVE complex is required for stable assembly of the yeast vacuolar proton-translocating ATPase (V-ATPase) during both biosynthesis of the enzyme and regulated reassembly of disassembled V 1 and V 0 sectors. It is not yet known how RAVE effects V-ATPase assembly. Previous work has shown that V 1 peripheral or stator stalk subunits E and G are critical for binding of RAVE to cytosolic V 1 complexes, suggesting that RAVE may play a role in docking of the V 1 peripheral stalk to the V 0 complex at the membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 49 publications
6
90
0
Order By: Relevance
“…Similarly, in the absence of RAVE, the C subunit has been found to be incapable of assembling into V-ATPase, resulting in the loss of enzyme activity (Smardon and Kane, 2007). These data are supported by findings by Keenan et al (2002), which showed a reduction of over 48% in catalytic activity that did not affect enzyme assembly in experimental models with different mutations in the C subunit.…”
Section: The C Subunitsupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, in the absence of RAVE, the C subunit has been found to be incapable of assembling into V-ATPase, resulting in the loss of enzyme activity (Smardon and Kane, 2007). These data are supported by findings by Keenan et al (2002), which showed a reduction of over 48% in catalytic activity that did not affect enzyme assembly in experimental models with different mutations in the C subunit.…”
Section: The C Subunitsupporting
confidence: 79%
“…In an in vitro study, Smardon and Kane (2007), found that while V1V0 assembly took place in the absence of the C subunit, the resulting complex was highly unstable and that V-ATPase activity was extremely low; this would suggest that the C subunit is exclusively responsible for regulating the assembly of the V1V0 complex. Similarly, in the absence of RAVE, the C subunit has been found to be incapable of assembling into V-ATPase, resulting in the loss of enzyme activity (Smardon and Kane, 2007).…”
Section: The C Subunitmentioning
confidence: 99%
See 1 more Smart Citation
“…Further complicating the understanding of this mechanism are the number of cellular binding partners for subunits likely to be involved in enzyme regulation. Subunit C, for example, has been shown to interact with kinases (47,50), actin (51), ATP (52), and the Regulator of the H ϩ -ATPase of vacuoles and endosomal membranes complex (53). Interestingly, the C subunit x-ray crystal structure was solved in two different conformations, but it remains unclear whether these changes may be linked to release of subunit C from the enzyme during regulated disassembly (18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dynamic interaction observed with the c subunit and trafficking to the plasma membrane suggests a role for HRG-1 in assembly or targeting of the V 0 domain to specific membranes. Regulation of V-ATPase assembly is not completely understood but has previously been shown to involve several different proteins, including the protein complex RAVE that regulates assembly of the V 1 domain in yeast (13), and chaperones for V 0 domain assembly (9).…”
Section: Discussionmentioning
confidence: 99%